Designing A Student Attendance Application Using Mit App Inventor - Achry Rafly Fadlillah; Ferdinandus Cilverius Ola Beda (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2023)
Education is the main foundation in community development and human resource development. In the context of higher education, the quality of the learning process and lecture management greatly affects student success. One aspect that has a significant impact on the learning process is student attendance management. Traditionally, recording student attendance is done manually by using a physical attendance list that must be filled in by students and signed by lecturers. Although it has been used for a long time, this method has a number of limitations that need to be overcome. In the rapidly evolving digital era, we have access to technology that can simplify and improve student attendance management. The use of information technology can provide a more efficient, accurate, and practical solution in recording student attendance. The app was developed using MIT App Inventor, a platform that makes it easy for users to create Android apps without in-depth programming knowledge.